The Colophon - Leichty, Erle
The Catch-Line. The Name of the Series and Number of the Tablet. The Number of Lines on the Tablet. The Source of the Copy. The Name of the Owner of the Tablet. The Name of the Scribe Making the Copy. The Reason for Making the Copy. The Curse or Blessing. The Date. Disposition of the Copy.